Manufacturing method for rare earth permanent magnet material

The method of deep cooling and tempering treatments effectively addresses the brittleness issue of rare earth permanent magnets, enhancing their mechanical strength while preserving magnetic performance, thus expanding their application scope.

JP2025512635AActive Publication Date: 2025-04-22NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023544780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-03-09
Filing Date
2023-03-13
Publication Date
2025-04-22
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

Rare earth permanent magnet materials exhibit high room temperature brittleness, making them difficult to process mechanically and limiting their applications due to susceptibility to cracking and demagnetization under impact and vibration.

Method used

A method involving one or more deep cooling treatments and tempering treatments is applied to rare earth permanent magnet materials, specifically after sintering and/or after tempering, to enhance mechanical properties without compromising magnetic performance.

Benefits of technology

The method significantly improves the bending strength and maintains excellent magnetic properties of rare earth permanent magnet materials, making them more suitable for applications requiring impact and vibration resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512635000001_ABST
    Figure 2025512635000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing a rare earth permanent magnet material, which includes one or more deep-cooling and tempering treatments. When the method includes one deep-cooling and tempering treatment, the deep-cooling is performed between the sintering and tempering treatments or after the tempering treatment. When the method includes two or more deep-cooling and tempering treatments, at least one deep-cooling is performed between the sintering and tempering treatments, and at the same time, at least one deep-cooling is performed after the tempering treatment. The method for producing a rare earth permanent magnet material has the advantages of fine structure, homogenized structure, and rapid and easy processing, and can effectively improve the mechanical properties of the rare earth permanent magnet material and maintain excellent magnetic properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of magnetic material manufacturing technology, and to a method for manufacturing rare earth permanent magnet materials. [Background technology]

[0002] Rare earth permanent magnet materials are widely used in many fields due to their excellent magnetic performance. However, like many intermetallic compounds, rare earth permanent magnet materials have a very large room temperature brittleness, which makes their mechanical processing difficult. The magnets are prone to cracking and edges falling off during use, which has a negative impact on the stability of permanent magnet devices. Therefore, the application of rare earth permanent magnet materials is limited in precision instruments and in areas with strict requirements for impact resistance and vibration resistance.

[0003] Currently, there are studies on improving mechanical properties by methods such as surface modification, element doping, and oxide addition. Although the mechanical properties have been improved, the magnetic properties are obviously degraded. Existing methods for improving the mechanical properties of rare earth permanent magnet materials sacrifice magnetic properties, and the processes are complicated and costly, making them difficult to apply to actual manufacturing processes.

[0004] Cryogenic treatment refers to the treatment of workpieces at temperatures below -130°C using liquid nitrogen as a refrigerant, and can significantly improve the mechanical properties of black metals and non-ferrous metals, but the application of cryogenic treatment to optimize the mechanical properties of rare earth permanent magnet materials has not been reported. Summary of the Invention

[0005] In response to the problem that rare earth permanent magnetic materials have high room temperature brittleness and existing methods for improving the mechanical properties of rare earth permanent magnetic materials sacrifice magnetic properties, the present invention provides a method for improving the mechanical properties of rare earth permanent magnetic materials, which can effectively improve the mechanical properties of rare earth permanent magnetic materials while maintaining excellent magnetic properties.

[0006] The object of the present invention is achieved by the following technical solutions: A method for producing a rare earth permanent magnet material, the method comprising one or more deep cooling and tempering treatments.

[0007] Preferably, the manufacturing method includes one deep-chilling and one tempering step, the deep-chilling being performed between the sintering and tempering steps, or the deep-chilling being performed after the tempering step.

[0008] Preferably, the manufacturing method includes two or more deep-chilling and tempering processes, at least one deep-chilling process being performed between the sintering process and the tempering process, while at least one deep-chilling process being performed after the tempering process.

[0009] Preferably, the manufacturing method includes two deep-chilling and tempering processes: a first deep-chilling process after sintering, then a tempering process, and then a second deep-chilling process.

[0010] Preferably, the manufacturing method includes three deep cooling and tempering steps.

[0011] Preferably, the sintering process is followed by a first deep-freezing process, then a tempering process, then a second deep-freezing process, and then a third deep-freezing process. Alternatively, a first deep-freezing treatment is performed after the sintering treatment, then a second deep-freezing treatment is performed, then a tempering treatment is performed, and then a third deep-freezing treatment is performed.

[0012] Preferably, the rare earth permanent magnet material is RFe 14 B series, SmCo5 series, Sm2Co 17 SmFe 17 N x series and 1:12 type rare earth permanent magnet material alloys.

[0013] Preferably, the manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, deep cooling, and tempering. Alternatively, the manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, tempering, and deep-cooling.

[0014] Preferably, the manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, and a second deep-cooling treatment.

[0015] Preferably, the manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, a second deep-cooling treatment, and a third deep-cooling treatment. Alternatively, the manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a second deep-cooling treatment, a tempering treatment, and a third deep-cooling treatment.

[0016] Preferably, the step of cryogenically treating includes placing the compact in a cryogenically treating system, cooling it down to a cryogenically treating temperature, and then removing it. Alternatively, the step of cryogenic treatment includes placing the compact directly in liquid nitrogen, cryogenically treating it, and then removing it.

[0017] Preferably, the deep-cooling temperature is ≦−130° C. and / or the deep-cooling time is 1 to 500 minutes.

[0018] Preferably, the deep-cooling temperature is ≦−160° C. and / or the deep-cooling time is 10 to 400 minutes.

[0019] Preferably, the deep-cooling temperature is ≦−190° C. and / or the deep-cooling time is 20 to 300 minutes.

[0020] Preferably, the tempering treatment is one of a tempering diffusion treatment, an ageing treatment, and a nitriding treatment.

[0021] Preferably, the tempering and diffusion treatment includes primary tempering at 800 to 950° C. for 2 to 6 hours, followed by cooling to 400 to 650° C. at a cooling rate of 0.3 to 1.3° C. / min and secondary tempering for 2 to 6 hours. The aging treatment involves maintaining the temperature at 800 to 950° C. for 10 to 25 hours, then lowering the temperature to 400 to 550° C. at a cooling rate of 0.3 to 1.3° C. / min, and maintaining the temperature for 2 to 12 hours. The nitriding treatment involves maintaining the temperature at 400 to 650° C. for 1 to 20 hours in nitrogen gas and / or ammonia gas.

[0022] Another object of the present invention is to provide a rare earth permanent magnet material produced by the above-mentioned production method.

[0023] Compared with the prior art, the present invention has the following advantages: 1. In the present invention, the first deep cooling treatment is carried out after sintering. The temperature reduction causes the volume of the compact to shrink, which leads to internal structural defects such as stress and dislocation. This is favorable for the precipitation and growth of the precipitation phase during the tempering process, and a uniform and complete structure and excellent magnetic properties can be obtained. 2. The present invention is advantageous in improving the bending properties of rare earth permanent magnet materials by performing a second deep cooling treatment after tempering. Compared with methods for improving mechanical properties such as surface modification, the method of the present invention is simpler and more effective, has lower cost, stronger operability, and is suitable for mass production. 3. The manufacturing method of rare earth permanent magnet material of the present invention includes two or more deep-cooling and tempering treatments, at least one deep-cooling treatment is performed between the sintering treatment and the tempering treatment, and at least one deep-cooling treatment is performed after the tempering treatment, which is favorable for improving the bending property and magnetic property of the material. 4. The method of the present invention for improving the mechanical properties of rare earth permanent magnet materials does not require the introduction of non-magnetic phases and does not degrade the magnetic properties, as compared with methods such as element doping or oxide addition. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic diagram showing the dimensions, orientation, and direction of force applied to a three-point bending test sample. [Diagram 2]FIG. 2 is a three-point bending curve diagram of the samarium-cobalt permanent magnet produced in Example 1 and the samarium-cobalt permanent magnet produced in Comparative Example 1. [Diagram 3] FIG. 2 is a demagnetization curve diagram of the samarium-cobalt permanent magnet produced in Example 1 and the samarium-cobalt permanent magnet produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, embodiments of the method for producing a rare earth permanent magnet material of the present invention will be described in detail, but these embodiments are merely illustrative and the disclosure of the present invention is not limited thereto.

[0026] A method for producing a rare earth permanent magnet material, the method comprising one or more deep cooling and tempering treatments.

[0027] In some embodiments of the present invention, the manufacturing method includes one deep-chilling and tempering treatment. The deep-chilling is performed between the sintering and tempering treatments, or after the tempering treatment. The manufacturing method includes a deep-chilling treatment after the sintering treatment and then a tempering treatment. Or, the manufacturing method includes a tempering treatment after the sintering treatment and then a deep-chilling treatment. Preferably, the manufacturing method includes a tempering treatment after the sintering treatment and then a deep-chilling treatment. When the manufacturing method includes one deep-chilling, the deep-chilling treatment is performed after the tempering treatment, which provides the rare earth permanent magnet material with better bending strength and magnetic properties.

[0028] In some embodiments of the invention, the manufacturing method includes two or more deep cooling and tempering processes, at least one deep cooling process being performed between the sintering and tempering processes, while at least one deep cooling process being performed after the tempering process.

[0029] In some embodiments of the present invention, the manufacturing method preferably includes two deep-cooling processes and a tempering process. Specifically, the first deep-cooling process is performed after the sintering process, then the tempering process is performed, and then the second deep-cooling process is performed. Through the two deep-cooling processes, the rare earth permanent magnet material has better bending strength and magnetic performance.

[0030] In some embodiments of the present invention, the manufacturing method includes three deep-chilling and tempering processes. Preferably, the manufacturing method includes a first deep-chilling process after a sintering process, then a tempering process, then a second deep-chilling process, and then a third deep-chilling process. Alternatively, the manufacturing method includes a first deep-chilling process after a sintering process, then a second deep-chilling process, then a tempering process, and then a third deep-chilling process.

[0031] In some embodiments of the present invention, the deep-chilling temperature is ≦-130°C, preferably, the deep-chilling temperature is ≦-160°C, and more preferably, the deep-chilling temperature is ≦-190°C.

[0032] In some embodiments of the present invention, the deep-cooling treatment time is 1 to 500 minutes, preferably 10 to 400 minutes, and more preferably 20 to 300 minutes.

[0033] In some embodiments of the present invention, the step of deep-cold treatment includes placing the compact into a deep-cold treatment system, performing deep-cold treatment when the temperature is reduced to a deep-cold treatment temperature, and then removing the compact. The compact removed from the deep-cold treatment system is warmed to room temperature before proceeding to the next step.

[0034] In some embodiments of the present invention, the step of deep-freezing includes placing the molded body directly in liquid nitrogen, performing the deep-freezing treatment, and then removing the molded body. The molded body removed from the liquid nitrogen is warmed to room temperature before proceeding to the next step.

[0035] In some embodiments of the present invention, the tempering temperature T2≧200°C, more preferably, the tempering temperature T2≧400°C.

[0036] In some embodiments of the present invention, the tempering treatment includes treatment at 800 to 950° C. for 2 to 25 hours, and then decreasing the temperature to 400 to 650° C. and treating for 2 to 15 hours.

[0037] In some embodiments of the present invention, the rare earth permanent magnet material is RFe 14 B-based (R is one or more of La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, and Y), SmCo5-based, Sm2Co 17 SmFe 17 N x The rare earth permanent magnet material may be in the form of a powder or a lump, and may be one of, but not limited to, one of the following rare earth permanent magnet material alloys: 1:12 type rare earth permanent magnet material alloys;

[0038] Rare earth permanent magnet material is R2Fe 14 For B-based rare earth permanent magnet alloys, the tempering process is a tempering diffusion process. 17 For rare earth permanent magnet material alloys of the SmFe system and 1:12 type, the tempering treatment is an aging treatment. 17 N x In the case of a rare earth permanent magnet material alloy, the tempering treatment is a nitriding treatment.

[0039] The tempering diffusion treatment includes primary tempering at 800-950°C for 2-6 hours, followed by cooling to 400-650°C at a cooling rate of 0.3-1.3°C / min and secondary tempering for 2-6 hours.

[0040] The aging treatment involves maintaining the temperature at 800 to 950°C for 10 to 25 hours, then lowering the temperature to 400 to 550°C at a cooling rate of 0.3 to 1.3°C / min, and maintaining the temperature for 2 to 12 hours.

[0041] The nitriding treatment involves maintaining the temperature at 400 to 650° C. for 1 to 20 hours in an atmosphere of nitrogen gas, ammonia gas, or a mixture of nitrogen gas and ammonia gas.

[0042] In some embodiments of the present invention, the process further includes blending raw materials, melting and refining, powder preparation, and oriented powder compaction prior to the sintering process.

[0043] In some embodiments of the present invention, the manufacturing method includes raw material blending, melting and refining, powder preparation, oriented powder compaction, sintering, deep cooling, and tempering.

[0044] In some embodiments of the present invention, the manufacturing method includes raw material blending, melting and refining, powder preparation, oriented powder compaction, sintering, tempering, and deep-cooling.

[0045] In some embodiments of the present invention, the manufacturing method includes raw material blending, melting and refining, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, and a second deep-cooling treatment.

[0046] In some embodiments of the present invention, the manufacturing method includes raw material blending, melting and refining, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, a second deep-cooling treatment, and a third deep-cooling treatment.

[0047] In some embodiments of the present invention, the manufacturing method includes raw material blending, melting and refining, powder preparation, oriented powder compaction, sintering, a first deep-freezing treatment, a second deep-freezing treatment, a tempering treatment, and a third deep-freezing treatment.

[0048] The steps of raw material mixing, melting and refining, powder preparation, oriented powder compaction, and sintering are not limited, and it is sufficient to use process steps commonly used in this field.

[0049] Specific steps of raw material mixing, melting and smelting, powder preparation, oriented powder compaction, and sintering are listed as follows.

[0050] Raw material blending: Each raw material is weighed and blended according to the stoichiometric ratio of the molecular formula of the rare earth permanent magnet material.

[0051] Melting and smelting: The mixed raw materials are placed in a vacuum melting and smelting furnace and melted and smelted at a temperature of 1200-1800°C. The melted raw materials form a homogeneous alloy solution, which is then poured into a cooled copper mold to obtain an alloy ingot.

[0052] Powder production: The alloy ingot is mechanically crushed into powder of 100 to 500 μm, and the powder is further pulverized into powder with an average particle size of 2 to 6 μm using a jet mill process.

[0053] Oriented powder compaction: Oriented compaction is performed under a magnetic field of 1 to 5 T. After sealing, a cold isostatic press is used to maintain a pressure of 150 to 200 MPa for 10 to 40 seconds to compact the powder to obtain a green body.

[0054] Sintering treatment: The compact is sintered at 1150-1250°C for 1-5 hours under inert gas protection, and then solution-treated at 1130-1210°C for 1-5 hours under inert gas protection, and then cooled to room temperature. Or, sintering treatment: Vacuum sintering at 1020-1100°C for 2-8 hours.

[0055] The technical solution of the present invention will be further described below through specific examples and the accompanying drawings, but it should be understood that the specific examples described herein are only used to help understand the present invention and are not intended to specifically limit the present invention. In addition, the accompanying drawings used in this specification are only used to better explain the disclosure of the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the examples of the present invention are raw materials commonly used in the art, and the methods used in the examples are conventional methods in the art. <Example 1>

[0056] Raw material composition: Sm2Co used in this embodiment 17The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 24.75% samarium, 49.70% cobalt, 18.97% iron, 4.37% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.6 μm using a jet mill process. Oriented powder compaction: Oriented powder compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 170 MPa for 20 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1206°C for 2 hours under argon gas protection, and then solution-treated at 1190°C for 2 hours under argon gas protection, and then air-cooled to room temperature. First deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 0.5 hours, after which it was taken out and placed in the air and allowed to warm up naturally. Aging treatment: Under argon gas protection, the material was aged at 840°C for 12 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 3 hours, and then air-cooled to room temperature to obtain a magnet. Second deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 1 hour, after which it was taken out and placed in the air and allowed to warm up naturally. <Example 2>

[0057] Raw material composition: Sm2Co used in this embodiment 17 The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 25.76% samarium, 57.23% cobalt, 6.72% iron, 7.23% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.5 μm using a jet mill process. Oriented powder compaction: Oriented compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 160 MPa for 25 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1233°C for 2 hours under argon gas protection, and then solution-treated at 1180°C for 2 hours under argon gas protection, and then air-cooled to room temperature. First deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 0.5 hours, after which it was taken out and placed in the air and allowed to warm up naturally. Aging treatment: Under argon gas protection, the material was aged at 840°C for 20 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 10 hours, and then air-cooled to room temperature to obtain a magnet. Second deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 1 hour, after which it was taken out and placed in the air and allowed to warm up naturally. <Example 3>

[0058] Raw material composition: Sm2Co used in this embodiment 17 The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 24.75% samarium, 49.70% cobalt, 18.97% iron, 4.37% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.6 μm using a ball mill process. Oriented powder compaction: Oriented powder compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 170 MPa for 20 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1206°C for 2 hours under argon gas protection, and then solution-treated at 1190°C for 2 hours under argon gas protection, and then air-cooled to room temperature. Aging treatment: Under argon gas protection, the material was aged at 840°C for 12 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 3 hours, and then air-cooled to room temperature to obtain a magnet. Deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 1 hour, after which it was taken out and placed in the air and allowed to warm up naturally. <Example 4>

[0059] Raw material composition: Sm2Co used in this embodiment 17 The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 24.75% samarium, 49.70% cobalt, 18.97% iron, 4.37% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.7 μm using a jet mill process. Oriented powder compaction: Oriented powder compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 170 MPa for 20 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1206°C for 2 hours under argon gas protection, and then solution-treated at 1190°C for 2 hours under argon gas protection, and then air-cooled to room temperature. First deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 0.5 hours, after which it was taken out and placed in the air and allowed to warm up naturally. Aging treatment: Under argon gas protection, the material was aged at 840°C for 12 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 3 hours, and then air-cooled to room temperature to obtain a magnet. Second deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 0.5 hours, then taken out and placed in air to be allowed to warm naturally. Third deep-freezing treatment: The molded body was again directly placed in liquid nitrogen and subjected to deep-freezing treatment for 1 hour, after which it was taken out and placed in the air and allowed to warm up naturally. <Example 5>

[0060] Raw material composition: Sm2Co used in this embodiment 17 The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 24.75% samarium, 49.70% cobalt, 18.97% iron, 4.37% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.6 μm using a jet mill process. Oriented powder compaction: Oriented powder compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 170 MPa for 20 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1206°C for 2 hours under argon gas protection, and then solution-treated at 1190°C for 2 hours under argon gas protection, and then air-cooled to room temperature. First cryogenic treatment: The molded body was placed in a cryogenic treatment system and cooled to -190°C at a temperature drop rate of 5°C / min. The molded body was then kept at this temperature for 0.5 hours, taken out and placed in the air to allow the temperature to rise naturally. Aging treatment: Under argon gas protection, the material was aged at 840°C for 12 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 3 hours, and then air-cooled to room temperature to obtain a magnet. Second cryogenic treatment: The molded body was placed in a cryogenic treatment system and cooled to -190°C at a temperature drop rate of 10°C / min., then kept at that temperature for 0.5 hours, taken out and placed in the air to allow the temperature to rise naturally. <Example 6>

[0061] Raw material composition: Sm2Co used in this embodiment 17 The raw material composition of the samarium-cobalt permanent magnet material was, in weight percent, 24.75% samarium, 49.70% cobalt, 18.97% iron, 4.37% copper, and the remainder zirconium, with the purity of Sm, Co, and Cu being ≧99.9%, and the purity of Fe and Zr being ≧99.5%. Melting and refining: The mixed raw materials were melted and refined in a vacuum high-frequency induction electric furnace, and high-purity argon gas was introduced. The melting and refining temperature was 1500°C. The melted raw materials formed a homogeneous alloy solution, which was then poured into a cooled copper mold to obtain an alloy ingot. Powder preparation: The ingots were mechanically crushed into powder of 100-300 μm, and the powder was further pulverized into powder with an average particle size of 4.6 μm using a jet mill process. Oriented powder compaction: Oriented powder compaction was performed under a magnetic field of 2 T. After sealing, a cold isostatic press was used to maintain a pressure of 170 MPa for 20 seconds to compact the powder, thereby obtaining a green body. Sintering and solution treatment: The compact was sintered at 1206°C for 2 hours under argon gas protection, and then solution-treated at 1190°C for 2 hours under argon gas protection, and then air-cooled to room temperature. First cryogenic treatment: The molded body was placed in a cryogenic treatment system and cooled to -190°C at a temperature drop rate of 10°C / min., then kept at that temperature for 0.5 hours, taken out and placed in the air to be allowed to warm up naturally. Aging treatment: Under argon gas protection, the material was aged at 840°C for 12 hours, then cooled to 400°C at a cooling rate of 0.5°C / min, kept at that temperature for 3 hours, and then air-cooled to room temperature to obtain a magnet. Second deep-freezing treatment: The molded body was directly placed in liquid nitrogen and subjected to deep-freezing treatment for 0.5 hours, then taken out and placed in air to be allowed to warm naturally. Third cryogenic treatment: The molded body was placed in a cryogenic treatment system and cooled to -194°C at a temperature drop rate of 10°C / min., and then kept at that temperature for 0.5 hours. It was then taken out and placed in the air to be allowed to warm up naturally. <Example 7>

[0062] The manufacturing method of the samarium-cobalt permanent magnet of Example 7 differs from Example 1 in that the compact is not subjected to a second deep cooling treatment after the aging treatment, but the rest is the same as Example 1. <Example 8>

[0063] The composition of the neodymium iron boron alloy used in this embodiment is (PrNd) 32 (CoCuAlZr) 0.2 The manufacturing process adopted was vacuum rapid solidification smelting-hydrogen crushing-powder preparation by jet mill-magnetic field orientation molding-cold isostatic pressing-sintering-first deep-freezing treatment-tempering treatment-second deep-freezing treatment. The jet-milled powder had an average particle size of 2.18 μm and was vacuum sintered at 1060 °C for 5 hours. The compact was directly placed in liquid nitrogen, removed after 0.5 hours to perform the first deep-freezing treatment, placed in air and allowed to warm naturally, and then tempered at 900 °C and 480 °C for 3 hours each (the temperature drop rate from 900 °C to 480 °C was 0.5 °C / min), then the compact was directly placed in liquid nitrogen, removed after 1 hour, placed in air and allowed to warm naturally, and performed the second deep-freezing treatment. <Example 9>

[0064] The manufacturing method of the neodymium iron boron permanent magnet of Example 9 differs from that of Example 8 in that the first deep cooling treatment is not performed on the compact after sintering. The rest is the same as that of Example 8. <Example 10>

[0065] The manufacturing method of the neodymium iron boron permanent magnet of Example 10 is different from that of Example 8 in that the compact is not subjected to a second deep cooling treatment after the tempering treatment. <Comparative Example 1>

[0066] The manufacturing method of the samarium-cobalt permanent magnet of Comparative Example 1 differs from that of Example 1 in that the compact is not subjected to a first deep-cooling treatment after sintering and solution treatment, and is not subjected to a second deep-cooling treatment after aging treatment. The rest is the same as that of Example 1. <Comparative Example 2>

[0067] The manufacturing method of the samarium-cobalt permanent magnet of Comparative Example 2 differs from that of Example 2 in that the compact is not subjected to the first deep-cooling treatment after sintering and solid-solution treatment, and is not subjected to the second deep-cooling treatment after aging treatment. The rest is the same as that of Example 2. <Comparative Example 3>

[0068] The manufacturing method of the neodymium iron boron permanent magnet of Comparative Example 3 is different from that of Example 8 in that the compact is not subjected to the first deep cooling treatment after sintering, and is not subjected to the second deep cooling treatment after tempering. The rest is the same as that of Example 8.

[0069] The bending strength at room temperature of the samarium-cobalt permanent magnets of Examples 1-7 and Comparative Examples 1-2 was tested. There were five mechanical test samples under each condition, and the average value was taken. The dimensions, orientation, and direction of force applied to the three-point bending experiment samples are shown in Figure 1. At the same time, the magnetic properties at room temperature of the samarium-cobalt permanent magnets of Examples 1-7 and Comparative Examples 1-2 were tested. The test results of bending strength and magnetic properties are shown in Table 1.

[0070] Table 1. Bending strength and magnetic properties of samarium-cobalt permanent magnets of Examples 1 to 7 and Comparative Examples 1 and 2 JPEG2025512635000002.jpg57170

[0071] FIG. 2 shows three-point bending curves of the samarium-cobalt permanent magnet produced in Example 1 and the samarium-cobalt permanent magnet produced in Comparative Example 1. With reference to Table 1 and FIG. 2 together, it can be seen that the bending strength of the deep-chilled samarium-cobalt permanent magnet is improved compared to the magnet that is not deep-chilled. As can be seen from Table 1, the average bending strength of Examples 1 to 6 is greater than 150 MPa, while the average bending strength of Comparative Examples 1 to 2 is less than 140 MPa. From the above experimental results, it becomes clear that the mechanical properties of the samarium-cobalt permanent magnet of the present invention can be effectively improved after deep-chilling. The samarium-cobalt permanent magnets of Examples 3 and 7 were deep-chilled only once, and had improved bending strength compared to Comparative Example 1 that was not deep-chilled, but the samarium-cobalt permanent magnet of Example 3 that was deep-chilled once after aging treatment exhibited better bending properties compared to the samarium-cobalt permanent magnet of Example 7 that was deep-chilled once after sintering solid solution.

[0072] FIG. 3 shows the demagnetization curves of the samarium-cobalt permanent magnet produced in Example 1 and the samarium-cobalt permanent magnet produced in Comparative Example 1. Referring to Table 1 and FIG. 3 together, the magnetic properties of the deep-chilled samarium-cobalt permanent magnet are slightly improved compared to the magnet that is not deep-chilled. From the above experimental results, it can be seen that the samarium-cobalt permanent magnet of the present invention maintains excellent magnetic properties even after deep-chilling. Among them, the samarium-cobalt permanent magnets of Examples 3 and 7 were subjected to deep-chilling only once, and their magnetic properties were relatively low.

[0073] The bending strength at room temperature of the neodymium iron boron rare earth permanent magnet materials of Examples 8 to 10 and Comparative Example 3 was tested. There were five mechanical test samples under each condition, and the average value was taken. At the same time, the magnetic properties at room temperature of the neodymium iron boron rare earth permanent magnet materials of Examples 8 to 10 and Comparative Example 3 were tested. The test results of bending strength and magnetic properties are shown in Table 1.

[0074] Table 2 Bending strength and magnetic properties of neodymium iron boron rare earth permanent magnet materials of Examples 8 to 10 and Comparative Example 3 JPEG2025512635000003.jpg29170

[0075] From Table 2, it can be seen that the magnetic properties of the cryogenically treated neodymium iron boron rare earth permanent magnet material are not significantly different from those of the non-cryogenically treated magnet, but the mechanical properties are improved.

[0076] Each aspect, example, and feature of the present invention should be considered in all respects as illustrative and not limiting of the invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0077] In the manufacturing method of the present invention, the order of each step is not limited to the order listed, and the change of each step is within the scope of protection of the present invention without the creative labor of a person skilled in the art. Also, two or more steps or operations may be performed simultaneously.

[0078] Finally, it should be noted that the specific examples described in this specification are not intended to limit the embodiments of the present invention, but are merely intended to illustrate the present invention. Those skilled in the art can make various modifications and supplements to the specific examples described, or replace them in a similar manner, and it is not necessary or possible to provide complete examples of all the embodiments here. These obvious modifications or variations derived from the essential spirit of the present invention still belong to the protection scope of the present invention, and it is against the spirit of the present invention to interpret them as additional restrictions.

Claims

1. A method for producing rare earth permanent magnet material, comprising one or more deep cooling and tempering treatments.

2. 2. The method according to claim 1, wherein the method includes one deep-chilling and one tempering, and the deep-chilling is performed between the sintering and the tempering, or the deep-chilling is performed after the tempering.

3. The manufacturing method according to claim 1, characterized in that the manufacturing method includes two or more deep-chilling and tempering treatments, at least one deep-chilling is performed between the sintering treatment and the tempering treatment, and at the same time, at least one deep-chilling is performed after the tempering treatment.

4. The manufacturing method according to claim 1, characterized in that the manufacturing method includes two deep-chilling processes and a tempering process, in which a first deep-chilling process is performed after a sintering process, then a tempering process is performed, and then a second deep-chilling process is performed.

5. The method according to claim 1 , further comprising three deep cooling and tempering steps.

6. After the sintering process, a first deep-chilling process is performed, followed by a tempering process, then a second deep-chilling process, and then a third deep-chilling process, or Alternatively, the manufacturing method according to claim 5, further comprising the steps of: performing a first deep-cooling treatment after the sintering treatment; then performing a second deep-cooling treatment; then performing a tempering treatment; and then performing a third deep-cooling treatment.

7. The rare earth permanent magnet material is R 2 Fe 14 B series, SmCo 5 System, Sm 2 Co 17 System, Sm 2 Fe 17 N x 2. The method of claim 1, wherein the rare earth permanent magnet material comprises one of the following alloys: 1:12 and 1:

13.

8. The manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, deep cooling, and tempering; Alternatively, the method according to claim 2, further comprising the steps of blending raw materials, melting and smelting, powder preparation, oriented powder compaction, sintering, tempering, and deep-cooling.

9. The method according to claim 4, characterized in that the method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, and a second deep-cooling treatment.

10. The manufacturing method includes raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-cooling treatment, a tempering treatment, a second deep-cooling treatment, and a third deep-cooling treatment; Alternatively, the manufacturing method according to claim 5, further comprising the steps of raw material blending, melting and smelting, powder preparation, oriented powder compaction, sintering, a first deep-freezing treatment, a second deep-freezing treatment, a tempering treatment, and a third deep-freezing treatment.

11. The step of deep-freezing includes placing the compact into a deep-freezing system, cooling it down to a deep-freezing temperature, deep-freezing it, and then removing it; Alternatively, the step of deep-freezing treatment includes placing the molded body directly in liquid nitrogen for deep-freezing treatment, and then removing the molded body from the liquid nitrogen.

12. The method according to any one of claims 1 to 10, characterized in that the deep-chilling temperature is ≦−130° C. and / or the deep-chilling time is 1 to 500 minutes.

13. The method according to any one of claims 1 to 10, characterized in that the deep-chilling temperature is ≦−160° C. and / or the deep-chilling time is 10 to 400 minutes.

14. The method according to any one of claims 1 to 10, characterized in that the deep-chilling temperature is ≦−190° C. and / or the deep-chilling time is 20 to 300 minutes.

15. The manufacturing method according to any one of claims 1 to 10, characterized in that the tempering treatment is one of a tempering diffusion treatment, an aging treatment, and a nitriding treatment.

16. The tempering and diffusion treatment includes a first tempering at 800 to 950°C for 2 to 6 hours, followed by a second tempering at a cooling rate of 0.3 to 1.3°C / min to 400 to 650°C for 2 to 6 hours; The aging treatment includes maintaining the temperature at 800 to 950°C for 10 to 25 hours, then lowering the temperature to 400 to 550°C at a cooling rate of 0.3 to 1.3°C / min, and maintaining the temperature for 2 to 12 hours; The method according to claim 15, wherein the nitriding treatment comprises maintaining the temperature at 400 to 650° C. for 1 to 20 hours in nitrogen gas and / or ammonia gas.

17. A rare earth permanent magnet material produced by the method according to claim 1.

Citation Information

Patent Citations

  • Method for preparing rare-earth permanent magnetic alloy powder

    CN109967748A

  • Cryogenic treatment method of nano permanent magnetic RE crystal material

    CN1487535A

  • A method for processing Nd-Fe-B permanent magnetic material

    CN1571079A

  • ********************ne*chi******* ****to***shi***ha***ne*****fu***to*ka*ke***te*******ni*no*** **se*ka*ke***ni*su*****fu***to

    JP1976096726A

  • Manufacture of r2co17 permanent magnet

    JP1981019603A